Teacher’s Techniques in Teaching English at Junior High School - Fatika Sari; Andi Rachmawati Syarif; Muflihun Muflihun (Jurnal Pendidikan dan Pengajaran, 2022)
This research aims to determine the techniques used by teachers in teaching English at SMPN 1 Barangka. The design of this study is qualitative descriptive using observation and interview. In collecting data through observation researcher used field notes to observe techniques applied the teachers in the teaching process and interview teachers. The subjects in this study was the seventh grade English teacher. The findings revealed that the techniques applied the teachers seventh grade are question and answer techniques, repetition drill techniques, memorization techniques, small group discussion techniques, and transformation drill techniques. These techniques aims to improve student’s English pronunciation, improve memory power or student’s English vocabulary, familiarize students using English, improve students understanding of teaching materials, and train student’s to think about solving a problem. The selection of the techniques was based on the student’s English skill.